The effects of palm tocotrienol rich fraction (TRF) on proatherosclerotic changes in aorta of rats fed a high methionine diet - Ku Zaifah, Norsidah; Ahmad Yusof, Asmadi; Ayob, Azizi; Yusuf, Kamisah (Lippincott Williams & Wilkins, 2009)
Hyperhomocysteinemia is a risk factor for cardiovascular diseases. It is associated with an increase in oxidative stress. We aimed to study the effects of palm tocotrienol rich fraction (palm TRF) on proatherosclerotic changes in aorta of rats fed a high methionine diet. Forty-two male Wistar rats were divided into six groups. The first group was the control. Groups two through six were fed 1% methionine diet for 10 weeks. From week six onward, folate (8 mg/kg diet) or palm TRF (30, 60 or 150 mg/kg diet) were added into the diet of groups three (M + Folate), four (M + TFR30), five (M + TRF60) and six (M + TRF150) respectively. Body weights were recorded weekly. No significant difference in body weight was recorded. Methionine diet (M) significantly raised the plasma homocysteine (tHcy level) and this was reduced by the supplementations of palm TRF at 150 mg/kg diet and folate. The dietary methionine increased aortic lipid peroxidation as shown by the increase in TBARS (604.0 +/- 51.0 pmol MDA/ mg protein, P < 0.05). - See more at: http://www.nursingcenter.com/lnc/JournalArticle?Article_ID=2412948&Journal_ID=1658605&Issue_ID=2412900#sthash.VqFndvF4.dpuf